Open science directory [electronic resource] (EBSCO Industries, Inc., 2002)
Search tool for open access journals and journals in special programs for developing countries. The Open Science Directory has been developed by EBSCO and the Hasselt University Library based upon a request by marine information management experts collaborating within the framework of the IOC?s (Intergovernmental Oceanographic Commission of UNESCO) IODE (International Oceanographic Data and Information Exchange) programme.